SISTEM INFORMASI E-MADING (SI-EMA) BERBASIS WEBSITE SEBAGAI SARANA PENYALURAN KREASI PADA LITERASI SEKOLAH - Hasan Basri; Muhamad Tabrani; Eko Budiyono (Politeknik Bisnis Indonesia, 2022)
An information system is a set of tools used to obtain and manage information. At this time, the use of information systems in everyday life is very much and varied. Many companies or institutions are switching from conventional systems to computerized systems. This is because information systems can simplify business processes from traditional or conventional systems. School wall magazines are an important facility for students and schools to convey important information related to education, talent development and student careers. However, over time, conventional wall magazines have many problems such as damaged information sheets and limited information display space, the information on display must be accessed. directly causing students to crowd to get information, limiting access rights to display information. By using a qualitative method, this study succeeded in developing a software called the e-mading information system (SI EMA). in a structured way, SI EMA can be explained using the waterfall method. The creation of a website-based wall magazine aims to add value and function to conventional wall magazines to become more efficient and of high quality. The SI EMA website has changed the publication of conventional papers to be computerized, the use of paper media or printed documents has become electronic media, articles or written works are not easily lost because they have been documented on the website, the appearance of written works has become more attractive. With this renewal, problems can be resolved properly and are able to help schools and students not only in obtaining information more effectively and efficiently but also as a creative means to express their creativity.